PELAKSANAAN PERJANJIAN SEWA MENYEWA PERLENGKAPAN RESEPSI PERNIKAHAN SECARA LISAN ANTARA PELAKU USAHA DENGAN KONSUMEN PADA PANJI WEDDING PEKANBARU - Yulia Pratiwi; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Leasing is an activity that commonly occurs in the community and is regulated in Articles1548 to 1600 of the Civil Code. Article 1548 of the Civil Code explains that a lease is anagreement in which one party binds itself to provide enjoyment of an item to another party for acertain period of time with the payment of an agreed price. Leasing creates rights and obligationsfor the parties, in the implementation of leasing wedding reception equipment at Panji WeddingPekanbaru, it cannot be separated from problems. The problem that often occurs is default by thetenant. In this thesis the author tries to examine the implementation of the rental agreement forwedding reception equipment verbally at Panji Wedding and examines the settlement of defaultdisputes carried out by the lessee to the lessor. The purpose of writing this thesis is to determinethe form and process of implementing the lease agreement and to determine the efforts to resolvethe default that occurred in this lease agreement.The research method used in this thesis is using sociological legal research methods,namely research on the effectiveness of applicable laws and living in society. The nature of thisresearch is descriptive, that is, it defines and describes systematically, the facts andcharacteristics of the object under study appropriately. The data sources used are primary,secondary and tertiary data sources. The data collection technique used in this research is to usethe interview method and literature study.Based on the results of the study, it can be seen that the implementation of the leaseagreement at Panji Wedding is carried out verbally without special conditions so that in the eventof a dispute there is no strong evidence. In this agreement there is a default or a broken promiseand a statement of negligence in accordance with Article 1238 of the Civil Code, negligencecommitted by the tenant causes losses to business actors so that in resolving disputes that occurbetween the tenant and the Panji Wedding, the settlement is carried out through non-litigationchannels by negotiating between the two sides.Keywords: Agreement Lease – Oral – Defaul